Family decision-making and youth financial decisions: evidence from financial capability - Sheilla Putri Agustin; Agustinus Numberi (Ifma Publishing, 2026)
This study examines the impact of financial capability – comprising financial awareness, experience, skills, and knowledge – on financial decision-making among youth in Jayapura, Papua, Indonesia, while exploring the moderating role of family decision-making dynamics. A total of 229 respondents aged 17 to 25 completed a structured questionnaire, and the data were analyzed using partial least squares structural equation modeling (PLS-SEM). The results indicate that financial awareness significantly enhances financial knowledge, which in turn is a strong predictor of sound financial decision-making. Financial experience contributes substantially to the development of financial skill; however, financial skills alone do not exert a direct influence on decision-making behavior. Notably, family decision-making significantly moderates the relationship between financial knowledge and financial decision-making, underscoring the importance of sociocultural context in shaping youth financial behavior. These findings highlight the necessity of comprehensive financial education programs that integrate both individual financial competencies and familial influences. This study contributes to the financial capability literature by emphasizing the role of family as a contextual factor in financial decision-making processes among young adults.